Coppini-samlingen fra papir til internet: En beretning om en anderledes kildeudgivelse - Jacobsen, Jens Peter (Danish Yearbook of Musicology, 2004)
The Coppini Collection – from paper to the Internet A different kind of source edition The article is an account of the work of publishing Aquilino Coppini’s madrigal collection Musica tolta from 1607 on the Internet (www.jpj.dk/coppini.htm). This comprises 24 madrigals – including 11 by Claudio Monteverdi – furnished by Coppini with Latin religious texts, free poetic compositions or adapted Biblical texts. The publication, originally planned in normal sheet music format, was launched on the Internet in 1998 and in the course of five years has had 36,000 visitors. The music, intended for practical use, and the detailed critical commentary, can be downloaded free, and the article gives an account of the many different factors, for example of a technical nature, that had to be considered during the work with the edition, and of the great advantages that such a publication form has proved to have over other more traditional forms.